1996
DOI: 10.1073/pnas.93.14.7369
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing of agrin regulates its binding to heparin alpha-dystroglycan, and the cell surface.

Abstract: Agrin is a basal lamina molecule that directs key events in postsynaptic differentiation, most notably the aggregation of acetylcholine receptors (AChRs) on the muscle cell surface. Agrin's AChR clustering activity is regulated by alternative mRNA splicing. Agrin splice forms having inserts at two sites (y and z) in the C-terminal region are highly active, but isoforms lacking these inserts are weakly active. The biochemical consequences of this alternative splicing are unknown. Here, the binding of four recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 40 publications
(61 reference statements)
5
64
0
Order By: Relevance
“…Because C -Ag 4,0 and C -Ag 0,0 lack AChR-clustering activity, their concentration in C OS-7 cell -conditioned media was determined using a two-site sandwich ELISA (Gesemann et al, 1995;O'Toole et al, 1996) using an anti-agrin monoclonal antibody Agr 530 [StressGen Hoch et al, 1994)] and a rabbit antiserum raised against a synthetic peptide corresponding to amino acids 1862-1893 of the mouse agrin sequence (Rupp et al, 1992). These antibodies recognize distinct epitopes common to all agrin isoforms.…”
Section: Methodsmentioning
confidence: 99%
“…Because C -Ag 4,0 and C -Ag 0,0 lack AChR-clustering activity, their concentration in C OS-7 cell -conditioned media was determined using a two-site sandwich ELISA (Gesemann et al, 1995;O'Toole et al, 1996) using an anti-agrin monoclonal antibody Agr 530 [StressGen Hoch et al, 1994)] and a rabbit antiserum raised against a synthetic peptide corresponding to amino acids 1862-1893 of the mouse agrin sequence (Rupp et al, 1992). These antibodies recognize distinct epitopes common to all agrin isoforms.…”
Section: Methodsmentioning
confidence: 99%
“…These include dystroglycan, glycoconjugates, integrins, HB-GAM/pleitrophin, heparan sulfate proteoglycans, N-CAM, and laminins (Bowe et al 1994;Campanelli et al 1994Campanelli et al , 1996Gee et al 1994;Sugiyama et al 1994;, 1997Mook-Jung & Gordon 1995;Storms et al 1996;Daggett et al 1996;Gesemann et al 1996;O'Toole et al 1996;Hopf & Hoch 1996;Denzer et al 1997). Several of these have been implicated in AChR clustering based on studies in culture myotubes, but none has been shown to be critical for postsynaptic differentiation in vivo (reviewed in .…”
Section: Agrin Signalingmentioning
confidence: 99%
“…When small peptides are inserted in these regions, the overall properties of agrin are modified significantly. Insertion of a four-amino-acid sequence at the y site confers heparin-binding properties (47). When the insertion is present, the binding of agrin to α-dystroglycan is inhibited by heparin.…”
Section: Expression and Functional Propertiesmentioning
confidence: 99%
“…By analogy to laminin and perlecan, this domain may self-assemble. Alternatively spliced variants of domain IV with insertion of small peptide sequences, 4-19 amino acid residues long, have been described (47). These short peptides can significantly influence the binding of agrin to heparin, α-dystroglycan, and the cell surface (46).…”
Section: General Structural Featuresmentioning
confidence: 99%